PORNOCHANCHADA EM QUATRO TAKES: CORPO, SOCIEDADE, ESTILO E CENSURA - Correa, William Bruno (2020)
This thesis analyzes the marginalized pornochanchanda movie genre, a genre of cinema in the Brazilian context of the 1970s. It seeks to understand how body representations can be a mirror of Brazilian society of that period, in which the population lived under a military regime, and in which artistic production suffered various kinds of censorship. I analyse two pornochanchadas: “A Super Fêmea”, and “Guerra Conjugal”. I discuss the theme from an approach that merges cinema and cultural history, in order to identify and discuss cinematographic perceptions of the time about the masculine, the feminine, the homosexual, the obese, the black, the poor, the rich, in short, all the perceptions that pornochanchada can produce and its senses.